Sintaksis Nyaru : Komposisi Musik Generatif dalam Ansambel Campuran - Gen Dekti Dekti; Rosmegawaty Tindaon; Zainal Warhat (Gestus Journal: Penciptaan dan Pengkajian Seni, 2021)
Sintaksis Nyaru is an artificial musical composition that departs from the musical event of the Nyaru mantra in the Asyeik Pumbaru Jikat ritual as a natural composition grammar. The concept of the work of Sintaksis Nyaru is an elaboration of the construction of a musical hierarchy of mantras using a Generative Music system approach which is realized in the formation of a Mixed Ensemble. Overall, this composition offers two types of branching regarding the sequence of musical events, namely the right branch indicates retention and depending on memory, the left branch indicates retention and depends on expectation. The method of creating works is divided into three stages. The first stage determines the placement of Composition and Intuition Grammar. Second, form a Sequence of Events (Musical Works). Third, determine the structural description of the work. There are five parts (Arch Form) of the local structure consisting of part I (protention), part II (retention), part III (complexity), part IV (retention), part V (re-protection). The conclusion resulting from the psychological distance of the horizontal and vertical dimensions obtained from the attraction value of the global structure is 29,397 with the direction of relaxing movement.Keywords: Asyeik Ritual, Mantra Nyaru, Generative Music, Arch Form, Mixed Ensemble